PERLINDUNGAN HUKUM TERHADAP INVESTOR BILA TERJADI INSIDER TRADING DALAM PASAR MODAL - Dwi Juliana, Made; Retno Murni, Prof. R.A.; Purwani, Ni Putu (Kertha Wicara : Journal Ilmu Hukum, 2013)
One type of a criminal in the capital market is the practice of insider trading. Insider trading is an act that involves a group of people in the capital market who deliberately exploit information that has not been released to investors with the maximum benefit goal. To prove insider trading in the trading at the capital market is difficult, this is because the legal evidence is difficult to acceptable. Therefore, the legal protection is very important for investor to solve the insider trading problems.
Keywords: Insider, Information, Investor, Legal Protection.